5g+4(-5+g)=1-g

Simple and best practice solution for 5g+4(-5+g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+4(-5+g)=1-g equation:


Simplifying
5g + 4(-5 + g) = 1 + -1g
5g + (-5 * 4 + g * 4) = 1 + -1g
5g + (-20 + 4g) = 1 + -1g

Reorder the terms:
-20 + 5g + 4g = 1 + -1g

Combine like terms: 5g + 4g = 9g
-20 + 9g = 1 + -1g

Solving
-20 + 9g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-20 + 9g + g = 1 + -1g + g

Combine like terms: 9g + g = 10g
-20 + 10g = 1 + -1g + g

Combine like terms: -1g + g = 0
-20 + 10g = 1 + 0
-20 + 10g = 1

Add '20' to each side of the equation.
-20 + 20 + 10g = 1 + 20

Combine like terms: -20 + 20 = 0
0 + 10g = 1 + 20
10g = 1 + 20

Combine like terms: 1 + 20 = 21
10g = 21

Divide each side by '10'.
g = 2.1

Simplifying
g = 2.1

See similar equations:

| Y/5+8=7 | | 1/4x-1/5(x-7)=5x | | 2x+1/3y=2 | | -18k-6k=6+18k | | 1/4x+y=5 | | 61+x=36 | | 108=2x+20+2x | | x^3+6x^2-7x-42=0 | | X/4+8=-16 | | 61+x=25 | | -6t-8=16 | | 15x+5y=30 | | 3x+5+2=2x+27 | | X-14.29=25 | | 6-3b=18 | | 4k+3-2k=k+3 | | 4+x/3=-1 | | 3x/15=64/125 | | 5-10x+8x=15 | | -5d-4=2d+6 | | 1w+3w=48 | | 13x+18=5-7(1-x) | | 20*50-5*50+1= | | 3x+x+4=12 | | 2(4x+4)=72 | | 10x-4=2x+q | | 3-4X(5*6)=23-4 | | 5/3m=19/12 | | Pt+Prt=A | | 2/5x+1/6x=3/10x+1/3 | | 1/64x^12-4m^10 | | 12x+29=8x-7 |

Equations solver categories